Unravelling a case of rare peritoneal encapsulation following blunt abdominal trauma: a case report - Muthulingam, Arun Prabhu; Padmanabhan, Senthilkumar (International Surgery Journal, 2019)
Peritoneal encapsulation (PE) is a rare condition that has been described interchangeably with sclerosing encapsulated peritonitis as well as abdominal cocoon. Here we report a case of perforative peritonitis following blunt injury abdomen in a 30-year-old male patient. Computed tomography (CT) of the abdomen showed pneumoperitoneum possibly gastrointestinal tract perforation. Exploratory laparotomy was performed and the entire small bowel was encapsulated in a peritoneal sac. Peritoneal sac was excised. Perforation was noted in the proximal jejunum and primary closure done. Post-operative recovery was uneventful. PE is an extremely rare congenital condition in which there is abnormal return of the midgut loop to the abdominal cavity in the early stages of development. The small intestine is thus covered by the original dorsal mesentery, forming the characteristic accessory peritoneal sac. Management of cases is difﬁcult as CT ﬁndings may not be characteristic and may only be diagnosed at laparotomy. A discussion of the case and review of the literature are presented.